Governing the Life Course through Lifelong Learning: A Multilevel and Multidimensional View - Parreira do Amaral Marcelo; Tikkanen Jenni (MDPI AG, 2022)
The life course in general, and the educational trajectories of young people in particular, comprise a high degree of complexity as they take place in iterative, recursive and interactive negotiation processes in which numerous actors, institutions and discourses are involved. In this paper, an attempt is made to combine two conceptual discussions—Life Course and Governance—bringing them to bear on the examination of how Lifelong Learning (LLL) policies have been used to govern young people’s life courses. The paper synthesizes different discussions of the complex relations among governance, discourses and structures of opportunity that impact the governing of the life course and particularly educational trajectories. It suggests that the combination of life course research and a governance perspective enables analyzing the governance of educational trajectories along discursive, institutional and relational dimensions of opportunity structures. Considering these various dimensions, the paper argues, allows us to attend to the social interactions, decision-making processes and processing mechanisms that precede and/or underlie educational processes and thus favor or complicate them. The contribution also critically discusses the implications of a governance perspective on life courses and closes with a discussion of the multidimensional and multilevel challenge of governing life course by means of LLL policies.